Clinical Outcomes in 55 Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Who Were Asymptomatic at Hospital Admission in Shenzhen, China - Wang, Yanrong (J Infect Dis, 2020)
An epidemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has spread unexpectedly in Wuhan, Hubei Province, China, since December 2019. There are few reports about asymptomatic contacts of infected patients identified as positive for SARS-CoV-2 through screening. We studied the epidemiological and clinical outcomes in 55 asymptomatic carriers who were laboratory confirmed to be positive for SARS-CoV-2 through nucleic acid testing of pharyngeal swab samples. The asymptomatic carriers seldom occurred among young people (aged 18–29 years) who had close contact with infected family members. In the majority of patients, the outcome was mild or ordinary 2019 novel coronavirus disease during hospitalization.